Poland : Toward a Strategic, Effective, and Accountable State - World Bank Group (World Bank, Washington, DC, 2017)
The pathway to shared prosperity in Poland is built around growth, inclusion, and sustainability objectives, but success will ultimately depend on a more strategic, effective, and accountable state. Poland has done remarkably well, boasting strong growth over three decades. Looking forward, this Systemic Country Diagnostic (SCD) argues that a new level of sophistication is required to meet the challenges of a rapidly aging population and evolving global economy. This includes developing a more strategic, effective, and accountable state that can facilitate a strong consensus around consistent policies to foster growth, inclusion, and sustainability. Continued productivity growth will depend on Poland’s ability to transition to an innovation-led growth model. This transition, in turn, will require improved consistency and commitment to sound policies, as well as improved coordination between the public and private sectors. Demographic trends make it critical for Poland to invest in its people, ensuring that everyone can participate and benefit from growth. To that end, policies must be consistent—both across sectors and between local and national government institutions—such that every person has equal opportunity, participates in the labor market, and is able to move to where they are most productive. To grow sustainably, a new social consensus will be needed to confront difficult trade-offs between the needs of an aging population and the associated fiscal costs. Similarly, Poland will need to weigh the fiscal and economic costs of transitioning to a low-emissions economy against the social and environmental costs associated with business as usual. Consensus will be needed to ensure consistency of policies around agreed-upon principles, commitment to staying the course, coordination across all stakeholders, and cooperation from the private sector based on trust in government.